Pengaruh Rasio Likuiditas dan Rasio Profitabilitas Terhadap Harga Saham - Laras Auditria Putri; Muhammad Iqbal Ramadhan (Politeknik Ganesha Medan, 2023)
Increased liquidity ratios and profitability ratios can give a positive signal to stock prices. This study aims to obtain an overview of the relationship between liquidity ratios and profitability ratios with prices. The research approach uses a quantitative approach using secondary data in the form of financial and annual reports. This research was conducted in all companies except the financial sector which was listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2019. The analysis technique used was multiple regression with STATA software. The liquidity ratio is proxied by the Cash Ratio, and Current Ratio (CR). Profitability ratio proxied ROE, ROS, EPS, . The results showed that the liquidity ratio and profitability ratio had a positive effect on stock prices. The higher the liquidity ratio and profitability ratio, it will lead to increasing stock prices.